Electrolytic capacitor and manufacturing method of the same

By using a porous structure anode body in the electrolytic capacitor and forming a multi-layer conductive polymer electrolyte layer, the heat shrinkage and stress problems caused by the increase in the thickness of the capacitor under high voltage are solved, and the high voltage resistance is increased and the leakage current is suppressed.

JP2025054541APending Publication Date: 2025-04-08PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023163633
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-26
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

While improving high-voltage resistance and reducing leakage current, existing electrolytic capacitors face problems such as heat shrinkage and stress, resulting in increased dielectric layer defects and leakage current.

Method used

An anode body with a surface porous structure is used to form a solid electrolyte layer with a thickness between 18.0 μm and 50.0 μm, and a conductive polymer layer above n-layer is formed by multiple treatments, and the thickness and number of layers of the electrolyte layer are controlled to reduce heat shrinkage stress and dielectric layer defects.

Benefits of technology

It realizes the increase of high-voltage resistance and the suppression of leakage current, while reducing the equivalent series resistance (ESR) and improving the overall performance of the capacitor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025054541000001_ABST
    Figure 2025054541000001_ABST
Patent Text Reader

Abstract

To suppress a leakage current while securing a high-voltage resistance property of an electrolytic capacitor.SOLUTION: An electrolytic capacitor contains at least one capacitor element containing: a positive electrode body that contains a porous part in at least front layer; a dielectric layer coating at least part of the front surface of the positive electrode body; and a solid electrolyte layer coating at least part of the dielectric layer. The solid electrolyte layer includes: a first part that is filled into a gap of the porous part in the positive electrode body having the dielectric layer; and a second part that is deviated from a main surface of the positive electrode body having the dielectric layer. The second part contains n or more conductive polymer layers onto one main surface of the positive electrode body having the dielectric layer, and n is an integer of two or more. A thickness Tt of the second part on the one main surface of the positive electrode body having the dielectric layer satisfies 18.0 μm≤Tt≤50.0 μm. Tt / n satisfies 9.0 μm≤Tt / n≤12.5 μm.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to electrolytic capacitors and methods for manufacturing the same. [Background technology]

[0002] The electrolytic capacitor includes a capacitor element, an exterior body that seals the capacitor element, and an external electrode that is electrically connected to the capacitor element. The capacitor element includes an anode body having an anode lead portion that includes a first end and a cathode forming portion that includes a second end, a dielectric layer formed on at least the surface of the cathode forming portion of the anode body, and a cathode portion that covers at least a portion of the dielectric layer. The cathode portion includes a solid electrolyte layer that includes a conductive polymer and covers at least a portion of the dielectric layer, and a cathode lead layer that covers at least a portion of the solid electrolyte layer. An electrolytic capacitor that includes a solid electrolyte layer that includes a conductive polymer is also called a solid electrolytic capacitor.

[0003] Patent Document 1 discloses a method for manufacturing a solid electrolytic capacitor having a capacitor element having a dielectric layer and a solid electrolyte layer, The formation of the solid electrolyte layer is a first step of applying a first conductive polymer solution in which fine particles of a conductive polymer are dispersed, and drying the applied solution to form a first conductive polymer layer; a second step of applying a coating solution containing at least one selected from an aromatic sulfonic acid having a carboxy group and a hydroxy group or two carboxy groups in one molecule, or a salt thereof, to the first conductive polymer layer, and drying the coating solution; a third step of applying a second conductive polymer solution in which fine particles of a conductive polymer are dispersed, and drying the applied solution to form a second conductive polymer layer; The present invention proposes a method for manufacturing a solid electrolytic capacitor, which includes the steps of:

[0004] Patent Document 2 discloses a sheet-shaped anode body having an anode lead-out portion including a first end and a cathode forming portion including a second end, a dielectric layer formed on at least the surface of the cathode forming portion of the anode body; a cathode portion covering at least a portion of the dielectric layer; and the cathode portion includes a solid electrolyte layer including a conductive polymer covering at least a portion of the dielectric layer, The present invention proposes an electrolytic capacitor in which, in a cross section perpendicular to a direction from the first end to the second end of the capacitor element at an arbitrary position in a portion on the first end side of the cathode portion, the ratio T1 / T2 of a thickness T1 of the solid electrolyte layer formed in a corner of the anode body to a thickness T2 of the solid electrolyte layer formed in a central portion of a main surface of the anode body is 0.8 or more and 1.7 or less. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2014 / 087617 [Patent Document 2] International Publication No. 2021 / 132223 Summary of the Invention [Problem to be solved by the invention]

[0006] It ensures high voltage resistance of electrolytic capacitors while suppressing leakage current. [Means for solving the problem]

[0007] One aspect of the present disclosure includes at least one capacitor element including an anode body including a porous portion at least in a surface layer, a dielectric layer covering at least a portion of a surface of the anode body, and a solid electrolyte layer covering at least a portion of the dielectric layer, the anode body has a first end and a second end opposite the first end, the solid electrolyte layer is formed on the second end side of the anode body having the dielectric layer, and has a first portion filling voids in the porous portion and a second portion protruding from a main surface of the anode body having the dielectric layer, the second portion includes n or more conductive polymer layers on one main surface of the anode body having the dielectric layer, n is an integer of 2 or more, At the second end, a thickness (Tt) of the second portion on one main surface of the anode body having the dielectric layer satisfies 18.0 μm≦Tt≦50.0 μm; The Tt / n relates to an electrolytic capacitor that satisfies 9.0 μm≦Tt / n≦12.5 μm.

[0008] Another aspect of the present disclosure is a method for producing an anode body comprising: a first step of preparing an anode body including a porous portion in at least a surface layer and having a first end and a second end opposite to the first end; A second step of forming a dielectric layer on at least a portion of the surface of the anode body; and a third step of forming a solid electrolyte layer covering at least a portion of the dielectric layer, the solid electrolyte layer is formed on the second end side of the anode body having the dielectric layer, and has a first portion filling voids in the porous portion and a second portion protruding from a main surface of the anode body having the dielectric layer, the second portion includes n or more conductive polymer layers on one main surface of the anode body having the dielectric layer, n is an integer of 2 or more, The third step comprises: a sub-step A of treating the second end side of the anode body having the dielectric layer with a first treatment liquid containing a first conductive polymer or a precursor thereof; a sub-step B of treating the second end side of the anode body with a second treatment liquid containing at least a cationic agent after the sub-step A; a sub-step C of treating the second end side of the anode body with a third treatment liquid containing a second conductive polymer and a water-soluble polymer after the sub-step B; a sub-step D of repeating the sub-steps B and C; At least the third step forms the solid electrolyte layer at the second end such that a thickness Tt of the second portion on one main surface of the anode body having the dielectric layer satisfies 18.0 μm≦Tt≦45.0 μm and Tt / n satisfies 9.0 μm≦Tt / n≦12.5 μm. Effect of the Invention

[0009] In the electrolytic capacitor, high voltage resistance can be ensured and leakage current can be suppressed. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a schematic cross-sectional view of an electrolytic capacitor according to an embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] In electrolytic capacitors with a solid electrolyte layer, if the solid electrolyte layer has a certain thickness, it is expected that leakage current will be reduced and high voltage resistance will be obtained compared to when the thickness is small. However, if the thickness of the solid electrolyte is further increased, a higher voltage resistance will be obtained, but thermal contraction will occur during the formation of the solid electrolyte, and the stress caused by this will cause defects in the dielectric layer, resulting in a large leakage current.

[0012] The solid electrolyte layer is formed, for example, by applying a treatment liquid containing a conductive polymer to an anode body having a dielectric layer and drying the treatment liquid, or by applying a treatment liquid containing a precursor (such as a monomer) of the conductive polymer and polymerizing the precursor. By repeating the application and drying (or polymerization) of the treatment liquid multiple times, the conductive polymer is laminated in layers, and the thickness of the entire solid electrolyte layer formed can be increased. However, since an interface resistance occurs between adjacent conductive polymer layers, the conductivity of the solid electrolyte layer decreases, and the equivalent series resistance (ESR) of the electrolytic capacitor increases. In addition, if the application and drying (or polymerization) of the treatment liquid are repeated multiple times, the number of steps increases, which is disadvantageous in terms of cost.

[0013] In view of the above, (1) an electrolytic capacitor according to one aspect of the present disclosure includes at least one capacitor element including an anode body including a porous portion at least in a surface layer, a dielectric layer covering at least a part of the surface of the anode body, and a solid electrolyte layer covering at least a part of the dielectric layer. The anode body has a first end and a second end opposite to the first end. The solid electrolyte layer is formed on the second end side of the anode body having the dielectric layer, and has a first portion filling the voids of the porous portion and a second portion protruding from a main surface of the anode body having the dielectric layer. The second portion includes n or more conductive polymer layers on one main surface of the anode body having the dielectric layer. n is an integer of 2 or more. At the second end, a thickness Tt of the second portion on one main surface of the anode body having the dielectric layer satisfies 18.0 μm≦Tt≦50.0 μm. Tt / n satisfies 9.0 μm≦Tt / n≦12.5 μm. In this specification, the conductive polymer layer mainly contained in the first portion may be referred to as a first conductive polymer layer, and the conductive polymer layer mainly contained in the second portion may be referred to as a second conductive polymer layer.

[0014] According to the electrolytic capacitor of the present disclosure, as described above, the thickness Tt of the second portion on the main surface of the solid electrolyte layer is in a specific range, and the ratio Tt / n is in a specific range, n≧2. As a result, leakage current can be suppressed and high voltage resistance can be obtained. Since the ratio Tt / n is relatively large, even if the number of layers n of the second conductive polymer layer is relatively small, the thickness Tt can be relatively large. Therefore, the stress applied to the dielectric layer due to the thermal contraction of the second conductive polymer layer accompanying the heating treatment (drying, etc.) when forming the second portion can be reduced, and leakage current can be suppressed. In addition, it is considered that the high voltage resistance is due to both the thickness Tt and the ratio Tt / n being relatively large. In addition, the electrolytic capacitor of the present disclosure can ensure low ESR. This is considered to be because the number of layers n of the second conductive polymer layer is relatively small, and the total value of the interfacial resistance between the second conductive polymer layers in the second portion can be reduced, and high conductivity of the second portion can be ensured. Note that the ratio Tt / n can be approximately considered as the average thickness of one layer of the conductive polymer layer in the second part.

[0015] (2) In the above (1), n may be 4 or less. In this case, since the total value of the interfacial resistance between the second conductive polymer layers can be further reduced, a lower ESR is more easily obtained.

[0016] (3) In the above (1) or (2), the thickness Tt may satisfy 20.0 μm < Tt. In this case, it is easier to ensure higher breakdown voltage resistance. Also, when the thickness Tt is large, due to the stress associated with thermal shrinkage, defects are likely to occur in the dielectric layer and the leakage current is likely to become significant. However, in the present disclosure, by the fact that the thickness Tt / n and the number of the second conductive polymer layers are within a specific range, even if the thickness Tt is relatively large at 20 μm < Tt ≦ 45.0 μm, the leakage current can be suppressed low.

[0017] (4) In any one of the above (1) to (3), the second part may contain a water-soluble polymer. The weight average molecular weight (Mw) of the water-soluble polymer may be 50,000 or more and 800,000 or less. When the second part contains a water-soluble polymer, a conductive polymer layer with a relatively uniform thickness is easily formed, and higher breakdown voltage resistance is obtained. When the Mw of the water-soluble polymer is within the above range, compared with the case outside the above range, even if the number of layers n is relatively small, the thickness Tt and the ratio Tt / n can be easily adjusted to the above range. Therefore, higher breakdown voltage resistance is obtained. Also, it is easier to further reduce the total value of the interfacial resistance between adjacent second conductive polymer layers. Since higher conductivity of the entire second part can be ensured, the ESR can be further reduced. Since the number of layers n can be made relatively small, it is easy to reduce the stress applied to the dielectric layer due to the thermal shrinkage of the second part, and it is easy to further reduce the leakage current. Also, when the Mw of the water-soluble polymer is 50,000 or more and 800,000 or less, it is easy to form a second conductive polymer layer with a relatively uniform film quality and thickness.

[0018] (5) In the above (4), the content of the water-soluble polymer in the second portion may be 10% by mass or more and 20% by mass or less. In this case, the effect of the water-soluble polymer is easily obtained. Therefore, higher voltage resistance and low ESR can be ensured, and leakage current can be further reduced.

[0019] (6) In any one of the above (1) to (5), the second portion may include at least one continuous or discontinuous layer interposed between adjacent conductive polymer layers (specifically, second conductive polymer layers). The continuous or discontinuous layer may include at least a cationic agent. When the second portion includes such a layer, it is easy to form a second conductive polymer layer having a relatively large thickness on this layer, and it is easy to reduce n. Therefore, it is easy to maintain the high conductivity of the second portion, and it is easy to obtain a lower ESR.

[0020] (7) The present disclosure also includes a method for manufacturing an electrolytic capacitor. The method for manufacturing an electrolytic capacitor includes a first step of preparing an anode body including a porous portion at least on a surface layer thereof and having a first end and a second end opposite to the first end, a second step of forming a dielectric layer on at least a part of the surface of the anode body, and a third step of forming a solid electrolyte layer covering at least a part of the dielectric layer. The solid electrolyte layer is formed on the second end side of the anode body having the dielectric layer, and includes a first portion filling the voids of the porous portion and a second portion protruding from a main surface of the anode body having the dielectric layer. The second portion includes n or more conductive polymer layers on one main surface of the anode body having the dielectric layer. n is an integer of 2 or more. And, the third step is a sub-step A of treating the second end side of the anode body having the dielectric layer with a first treatment liquid containing a first conductive polymer or a precursor thereof; a sub-step B of treating the second end side of the anode body with a second treatment liquid containing at least a cationic agent after the sub-step A; a sub-step C of treating the second end side of the anode body with a third treatment liquid containing a second conductive polymer and a water-soluble polymer after the sub-step B; a sub-step D of repeating the sub-steps B and C; By the third step, the solid electrolyte layer is formed at the second end such that a thickness Tt of the second portion on one main surface of the anode body having the dielectric layer satisfies 18.0 μm≦Tt≦45.0 μm and Tt / n satisfies 9.0 μm≦Tt / n≦12.5 μm.

[0021] In the electrolytic capacitor obtained by the above manufacturing method, the thickness Tt of the second portion is within a specific range, and the ratio Tt / n is within a specific range, where n is greater than or equal to 2. Therefore, as described above, in the electrolytic capacitor, the ESR is kept low, leakage current is suppressed, and high voltage resistance is obtained.

[0022] (8) Regarding the above (7), in the sub-step D, the sub-step B and the sub-step C may be repeated (n-1) times. In this case, it becomes easier to adjust the thickness Tt of the second portion within the above range, and high voltage resistance is more likely to be obtained.

[0023] (9) In the above (7) or (8), the n may be equal to or greater than 2 and equal to or less than 4. In this case, the total value of the interfacial resistance between the second conductive polymer layers can be further reduced, making it easier to obtain a lower ESR.

[0024] (10) In any one of the above (7) to (9), the Mw of the water-soluble polymer may be 50,000 or more and 800,000 or less. In this case, the number of layers n is relatively small, and the thickness Tt and the ratio Tt / n can be easily adjusted to the above range. Therefore, high voltage resistance can be obtained and leakage current can be further easily suppressed. In addition, high conductivity of the second portion can be obtained, so that the ESR can be further reduced.

[0025] (11) In any one of the above (7) to (10), the concentration of the water-soluble polymer in the third treatment liquid may be 1% by mass or more and 15% by mass or less. This allows the second portion to contain the water-soluble polymer at an appropriate content, thereby ensuring higher voltage resistance and low ESR and further reducing leakage current.

[0026] The electrolytic capacitor and the manufacturing method thereof according to the present disclosure, including the above (1) to (11), are described in more detail below. At least one selected from the components described below can be arbitrarily combined with at least one of the above (1) to (11) relating to the electrolytic capacitor or the manufacturing method thereof according to the present disclosure, as long as such combination is technically possible.

[0027] [Electrolytic capacitor] The electrolytic capacitor comprises at least one capacitor element.

[0028] (Capacitor element) The capacitor element includes an anode body, a dielectric layer covering at least a portion of the surface of the anode body, and a cathode portion covering at least a portion of the dielectric layer. The cathode portion includes a solid electrolyte layer covering at least a portion of the dielectric layer.

[0029] (Anode body) The anode body may contain, for example, a valve metal, an alloy containing a valve metal, or a compound containing a valve metal (such as an intermetallic compound). These materials may be used alone or in combination of two or more. Examples of the valve metal include aluminum, tantalum, niobium, and titanium.

[0030] The anode body may be a foil (anode foil) of the above material.The anode body may be a compact (porous compact) of particles of the above material or a sintered body (porous sintered body) thereof.

[0031] The anode body has a first end and a second end opposite to the first end. The anode body includes, for example, an anode lead portion including the first end and a cathode forming portion including the second end. A cathode portion including a solid electrolyte layer is formed on a surface of a portion of the anode body on the second end side (specifically, the cathode forming portion). The anode lead portion is used, for example, for electrical connection with an external electrode on the anode side. An anode lead terminal may be connected to the anode lead portion.

[0032] The anode body includes a porous portion at least in the surface layer. The porous portion includes many fine voids. The porous portion provides the anode body with a fine uneven shape at least on the surface, which increases the surface area and provides a high capacity. The porous portion may be formed in a part of the surface layer of the anode body, or may be formed in the entire surface layer. When the anode body is an anode foil, the porous portion may be formed, for example, in at least the surface layer of the cathode forming portion, or may be formed in at least a part of the surface layer of the anode lead portion in addition to the surface layer of the cathode forming portion. When the anode body is a porous molded body or a porous sintered body, the entire anode body may constitute the porous portion.

[0033] When the anode body is an anode foil, the porous portion is formed by roughening the surface of at least a portion of a base material (e.g., metal foil) containing a valve metal, the portion corresponding to the cathode forming portion. The roughening may be performed by etching or the like.

[0034] For example, an anode body having a sheet-like or rectangular parallelepiped shape usually has six faces that determine the outer shape of the anode body. Of these faces, the faces (usually a pair of faces) that occupy the largest area are sometimes referred to as main faces, and the faces other than the main faces are sometimes referred to as end faces. For example, when the anode body is an anode foil, it has a pair of main faces that occupy most of the area of ​​the anode foil and an end face that exists between the pair of main faces. Even if the anode body has a notch or unevenness in part, the faces (usually a pair of faces) that occupy the largest area are sometimes referred to as main faces, and the faces other than the main faces are sometimes referred to as end faces, similar to the above.

[0035] In this specification, the direction from the first end to the second end when the anode body (such as an anode foil) is flat may be referred to as the length direction of the anode body. The direction from the first end to the second end is a direction parallel to the line connecting the center of the end face of the first end and the center of the end face of the second end. This direction may be referred to as the length direction of the anode body or capacitor element. Also, the direction perpendicular to the length direction and thickness direction of the anode body (or capacitor element) may be referred to as the width direction of the anode body (or capacitor element).

[0036] (Dielectric layer) The dielectric layer is an insulating layer that functions as a dielectric. The dielectric layer is made of a material that functions as a dielectric.

[0037] The dielectric layer contains, for example, a metal oxide as a material that functions as a dielectric. For example, when the anode body contains tantalum as a valve metal, the dielectric layer contains Ta2O5. When the anode body contains aluminum as a valve metal, the dielectric layer contains Al2O3. However, the dielectric layer is not limited to these and may be any material that functions as a dielectric.

[0038] The dielectric layer is formed along the inner wall surfaces of the holes and depressions (pits) on the surface of the anode body, including the inner wall surfaces of the holes in the porous portion. The surface of the dielectric layer has a fine uneven shape according to the shape of the surface of the porous portion.

[0039] (cathode) The cathode section includes at least a solid electrolyte layer covering at least a portion of the dielectric layer. The solid electrolyte layer is formed on the portion of the anode body on the second end side (in other words, the cathode formation portion) via a dielectric layer. The cathode section usually includes a solid electrolyte layer covering at least a portion of the dielectric layer, and a cathode extraction layer covering at least a portion of the solid electrolyte layer. The solid electrolyte layer and the cathode extraction layer will be described below.

[0040] (Solid electrolyte layer) The solid electrolyte layer is formed on the second end side of the anode body having the dielectric layer, and has a first portion filling the voids of the porous portion in the anode body having the dielectric layer and a second portion protruding from a main surface of the anode body having the dielectric layer.

[0041] Each of the first and second parts of the solid electrolyte layer is composed of a conductive polymer (such as a conjugated polymer and a dopant). Each of the first and second parts may include a conductive polymer layer. The solid electrolyte layer or the conductive polymer layer may further include an additive, if necessary.

[0042] The conjugated polymer may be a known conjugated polymer used in a solid electrolytic capacitor, such as a π-conjugated polymer. The conjugated polymer may be, for example, a polymer having a basic skeleton of polypyrrole, polythiophene, polyaniline, polyfuran, polyacetylene, polyphenylene, polyphenylenevinylene, polyacene, or polythiophenevinylene. Of these, a polymer having a basic skeleton of polypyrrole, polythiophene, or polyaniline is preferred. The above polymer may contain at least one monomer unit constituting the basic skeleton. The monomer unit may also include a monomer unit having a substituent. The above polymer may also include a homopolymer and a copolymer of two or more monomers. For example, polythiophene may include poly(3,4-ethylenedioxythiophene) (PEDOT).

[0043] The substituents are alkyl groups (C such as methyl and ethyl groups). 1-4 Alkyl groups, alkoxy groups (methoxy groups, ethoxy groups, etc.) 1-4 Alkoxy groups, hydroxy groups, hydroxyalkyl groups (hydroxy C such as hydroxymethyl groups) 1-4 Preferred are, but are not limited to, alkyl groups, etc. When each of the pyrrole compound, the thiophene compound, and the aniline compound has two or more substituents, the respective substituents may be the same or different.

[0044] Each of the first and second parts may contain one type of conjugated polymer or a combination of two or more types. Each of the first and second parts may contain one type of dopant or a combination of two or more types.

[0045] The weight average molecular weight (Mw) of the conjugated polymer is not particularly limited, but is, for example, 1,000 or more and 1,000,000 or less.

[0046] In this specification, the weight average molecular weight (Mw) is a value calculated as polystyrene measured by gel permeation chromatography (GPC). GPC is usually measured using a polystyrene gel column and water / methanol (volume ratio 8 / 2) as the mobile phase.

[0047] The dopant may be at least one selected from the group consisting of anions and polyanions.

[0048] Examples of anions include, but are not limited to, sulfate ions, nitrate ions, phosphate ions, borate ions, organic sulfonate ions, and carboxylate ions. When the dopant is an anion, for example, a relatively low molecular compound that generates an anion is used. Examples of dopants that generate sulfonate ions include sulfonic acid compounds such as aromatic sulfonic acid compounds. Examples of aromatic sulfonic acid compounds include benzenesulfonic acid, p-toluenesulfonic acid, and naphthalenesulfonic acid. The sulfonic acid compounds may be used alone or in combination of two or more.

[0049] Specific examples of polyanions include polyvinyl sulfonic acid, polystyrene sulfonic acid, polyallyl sulfonic acid, polyacryl sulfonic acid, polymethacryl sulfonic acid, poly(2-acrylamido-2-methylpropane sulfonic acid), polyisoprene sulfonic acid, and polyacrylic acid. These may be used alone or in combination of two or more. These may be polymers of a single monomer or copolymers of two or more monomers. Among these, polyanions derived from polystyrene sulfonic acid are preferred.

[0050] The amount of the dopant contained in each of the first and second parts may be, for example, 10 parts by mass or more and 1000 parts by mass or less, and may be 20 parts by mass or more and 500 parts by mass or less, relative to 100 parts by mass of the conjugated polymer.

[0051] In each of the first and second parts, the anionic group of the dopant may be contained in a free form, an anion form, or a salt form, or may be contained in a form bound to or interacting with the conjugated polymer. In this specification, all of these forms may be simply referred to as an "anionic group," "sulfonic acid group," "carboxy group," or the like.

[0052] Each of the first part and the second part may contain one water-soluble polymer or a combination of two or more water-soluble polymers. Since a treatment liquid containing a water-soluble polymer tends to have a high viscosity, it is preferable that the first part does not contain a water-soluble polymer, or if it does contain a water-soluble polymer, the content of the water-soluble polymer is low. The content of the water-soluble polymer in the first part may be, for example, 5% by mass or less or 1% by mass or less. On the other hand, when the second part contains a water-soluble polymer, it is preferable because the voltage resistance can be further increased and the leakage current can be further suppressed.

[0053] Examples of the water-soluble polymer include water-soluble polymer compounds having a hydrophilic group in the main chain or side chain. Examples of the hydrophilic group of the water-soluble polymer include a polyoxyalkylene chain, a hydroxy group, and an acid group (such as a carboxy group or a sulfonic acid group). A component having a lower electron-withdrawing ability than the dopant is usually used as the water-soluble polymer. Examples of such water-soluble polymer include a water-soluble polymer having at least one hydrophilic group (first hydrophilic group) selected from the group consisting of a carboxy group, a hydroxy group, and a polyoxyalkylene chain. A water-soluble polymer having a first hydrophilic group and a sulfonic acid group may be used, or a water-soluble polymer not containing a sulfonic acid group may be used. Examples of the polyoxyalkylene chain include polyoxy C 2-3 Examples of the water-soluble polymer include at least one selected from the group consisting of polyalkylene glycol compounds, water-soluble polyurethanes, water-soluble polyamides, water-soluble polyimides, water-soluble acrylic resins, and polyvinyl alcohols. The water-soluble polymer preferably has at least a plurality of carboxy groups. Examples of such water-soluble polymers include polymer-type polycarboxylic acids, resins into which a plurality of carboxy groups have been introduced (such as water-soluble polyurethane resins, water-soluble polyamides, water-soluble polyimides, and water-soluble acrylic resins).

[0054] The water-soluble acrylic resin also includes, for example, acrylic polymer-type polycarboxylic acids. Examples of such polymer-type polycarboxylic acids include polyacrylic acid, polymethacrylic acid, copolymers using at least one of acrylic acid and methacrylic acid (acrylic acid-methacrylic acid copolymers, copolymers of at least one selected from the group consisting of acrylic acid and methacrylic acid with other copolymerizable monomers, etc.). Examples of other copolymerizable monomers include acrylic acid esters (alkyl esters, hydroxyalkyl esters, etc.), methacrylic acid esters (alkyl esters, hydroxyalkyl esters, etc.), vinyl compounds (vinyl cyanide, olefins, aromatic vinyl compounds, etc.), polycarboxylic acids having polymerizable unsaturated bonds (maleic acid, fumaric acid, etc.) or acid anhydrides thereof. The copolymer may contain one type of monomer unit derived from other copolymerizable monomers, or may contain two or more types.

[0055] The acid groups such as carboxyl groups and sulfonic acid groups of the water-soluble polymer may be contained in the solid electrolyte layer in the form of a free group, an anion, or a salt, as in the case of the dopant. Also, some of the acid groups may be contained in the solid electrolyte layer in the form of a bond or interaction with a conjugated polymer. In this specification, all of these forms of carboxyl groups may be simply referred to as "carboxyl groups", and all of these forms of sulfonic acid groups may be simply referred to as "sulfonic acid groups".

[0056] The Mw of the water-soluble polymer is, for example, from 1000 to 1,000,000, may be from 10,000 to 800,000, and is preferably from 50,000 to 800,000.

[0057] In the solid electrolyte layer, at least one continuous or discontinuous layer may be interposed between adjacent conductive polymer layers. The continuous or discontinuous layer may contain at least a cationic agent. The continuous or discontinuous layer may contain a cationic agent and an anionic agent. The continuous or discontinuous layer may further contain a surfactant, if necessary. Here, a component other than the cationic agent and the anionic agent is used as the surfactant. More specifically, the continuous or discontinuous layer is interposed between adjacent first conductive polymer layers, between the first conductive polymer layer and the second conductive polymer layer, and between adjacent second conductive polymer layers. By providing such a continuous or discontinuous layer, it is easy to attach a large amount of conductive polymer to the conductive polymer layer, and the film-forming property of the conductive polymer layer can be improved. In particular, when the second portion includes such a continuous or discontinuous layer, even if the number n of the second conductive polymer layers is relatively small, the thickness Tt and the ratio Tt / n can be increased, and it is easy to adjust them to the above range. When an anionic agent is used, the dissociation property of the cationic agent can be increased in the treatment liquid (second treatment liquid) for forming a continuous or discontinuous layer, and the film-forming property of the conductive polymer layer is further improved.

[0058] The cationic agent has a cationic group. The cationic agent is not particularly limited as long as it can generate a cation in a dissociated state. Examples of the cationic agent include organic compounds (such as organic bases) containing an N element and metal compounds (such as inorganic bases such as metal hydroxides). As the cationic group of the cationic agent that is an organic compound, an amino group (such as a primary amino group, a secondary amino group, and a tertiary amino group) and a quaternary ammonium group are preferable. Such cationic groups also include salts of amino groups and salts of quaternary ammonium groups. Each of the first part and the second part may contain one type of cationic agent, or may contain two or more types of cationic agents.

[0059] Specific examples of the cationic agent include diamines (1,4-diaminobutane, 1,6-diaminohexane, 1,8-diaminooctane, 1,10-diaminodecane, diaminocyclohexane, diaminobenzene, diaminonaphthalene, etc.) and tertiary amines (N,N-dimethylhexylamine, N,N-dimethyloctylamine, N,N-diethyloctylamine, etc.). However, the cationic agent is not limited to these.

[0060] Each of the first and second parts may contain the cationic agent in any form of an amine compound, a cation corresponding to the amine compound, a quaternary ammonium compound, or a salt of a cation. For example, in each of the first and second parts, the cationic agent may form a salt with the anionic agent or may interact with the dopant.

[0061] The anionic agent has an anionic group. For example, at least one selected from the group consisting of anions and polyanions exemplified as the dopants of the first conductive polymer and the second conductive polymer may be used as the anionic agent. An anionic agent having a lower electron-withdrawing ability than the dopants of each conductive polymer may be used as the anionic agent. Each of the first part and the second part may contain one type of anionic agent, or may contain two or more types of anionic agents.

[0062] In each of the first and second parts, the anionic group of the anionic agent may be contained in any form selected from the above-mentioned anionic groups, anions corresponding to the above-mentioned anionic groups, and salts of anions.

[0063] Examples of the anionic agent include sulfonic acid compounds (methanesulfonic acid, benzenesulfonic acid, styrenesulfonic acid, etc.), phosphonic acid compounds (phenylphosphonic acid, etc.), carboxylic acids (salicylic acid, phthalic acid, etc.), hydroxyalkyl esters of carboxylic acids (hydroxyethyl acrylate, hydroxyethyl methacrylate, etc.), and phenolic compounds. Anionic agents having two or more kinds of anionic groups may also be used. Examples of such anionic agents include sulfosuccinic acid, sulfobenzoic acid, sulfosalicylic acid, disulfosalicylic acid, sulfophthalic acid, sulfoisophthalic acid, sulfoterephthalic acid, naphtholsulfonic acid, 2-(dihydroxyphosphinyloxy)acrylic acid, phosphonoacrylic acid, and 2-methyl-3-phosphonoacrylic acid.

[0064] A polymer type anionic agent may be used. Examples of such anionic agents include acid phosphooxy polyoxyalkylene glycol monoacrylates (acid phosphooxy polyoxyethylene glycol mono(meth)acrylates (P(=O)(OH)2-(O-CH2CH2)) of carboxylic acids such as acid phosphooxy ethyl acrylate and acid phosphooxy ethyl methacrylate. n -OC(=O)-CR=CH2) (n is an integer of 2 to 10, and R is a hydrogen atom or a methyl group), and aliphatic phosphonic acids (vinyl phosphonic acid, etc.).

[0065] The surfactant contained in the continuous or discontinuous layer may be either a nonionic surfactant or an ionic surfactant. Ionic surfactants include cationic surfactants, anionic surfactants, and amphoteric surfactants. The continuous or discontinuous layer may contain one type of surfactant or a combination of two or more types of surfactants.

[0066] Each of the first and second parts may further include at least one selected from the group consisting of known additives and known conductive materials other than conductive polymers, as necessary. Examples of the conductive material include at least one selected from the group consisting of conductive inorganic materials such as manganese dioxide and TCNQ complex salts. In addition, a layer for enhancing adhesion may be interposed between the dielectric layer and the first part (or the first conductive polymer layer).

[0067] (Part 1) The conductive polymer (first conductive polymer) contained in the first portion is formed, for example, using a treatment liquid (first treatment liquid) containing the first conductive polymer or a precursor thereof. The first conductive polymer is filled in the voids of the porous portion of the anode body so as to cover at least a part of the dielectric layer.

[0068] In the first portion, the first conductive polymer layer may be a single layer or multiple layers. When the first portion is composed of multiple first conductive polymer layers, the first conductive polymers contained in each layer may be the same or different.

[0069] When the second portion is formed using a treatment liquid (second treatment liquid) containing the second conductive polymer, the second conductive polymer may enter the voids of the porous portion of the anode body having a dielectric layer. Therefore, the first portion may contain the second conductive polymer. Also, the first conductive polymer may adhere to the surface of the convex portion of the porous portion of the anode body having a dielectric layer, and the second conductive polymer layer may be laminated on the adhered first conductive polymer. Therefore, the second portion may contain the first conductive polymer.

[0070] (Second part) The second portion includes n or more conductive polymer layers (second conductive polymer layers) on one main surface of the anode body having a dielectric layer. n is an integer of 2 or more. If n is less than 2, it is difficult to adjust the thickness Tt and the ratio Tt / n of the second portion to a predetermined range. n may be 5 or less, or may be 4 or less. In this disclosure, even if n is relatively small, a certain degree of thickness Tt in the second portion can be ensured. Therefore, while ensuring a low ESR, high voltage resistance can be obtained and leakage current can be suppressed.

[0071] In each of the second conductive polymer layers included in the second portion, the type, composition, content, etc. of the conductive polymer, additive, etc. may be the same or different.

[0072] The thickness Tt of the second portion satisfies 18.0 μm≦Tt≦50.0 μm. Tt is preferably Tt>20.0 μm, and more preferably Tt≧22.0 μm. By setting Tt in this range, high voltage resistance can be obtained. Even if the number of layers n is small, by setting the thickness Tt in this range, the total value of the interfacial resistance between the second conductive polymer layers in the second portion can be reduced, and the ESR can be kept low. If the thickness Tt exceeds 50.0, defects are likely to occur in the dielectric layer due to stress accompanying thermal contraction when forming the second portion, and leakage current is likely to become significant. On the other hand, by setting the thickness Tt to 50.0 μm or less, leakage current can be reduced. From the viewpoint of further suppressing leakage current, the thickness Tt may be 45.0 μm or less.

[0073] Thickness Tt is 18.0μm≦Tt≦50.0μm (or 45.0μm), 20.0μm <Tt≦50.0μm(または45.0μm)、あるいは22.0μm≦Tt≦50.0μm(または45.0μm)であってもよい。

[0074] The ratio Tt / n satisfies 9.0 μm≦Tt / n≦12.5 μm. When Tt / n is less than 9.0 μm, the number of layers n needs to be increased to keep the thickness Tt within the above range, and the total value of the interface resistance increases, resulting in a high ESR. The ratio Tt / n may be Tt / n≧9.5 μm or Tt / n≧9.8 μm. With the ratio Tt / n in this range, the ESR can be further reduced. The ratio Tt / n may be Tt / n≦12.0 μm or Tt / n≦11.5 μm. When the ratio Tt / n is in this range, it is easy to adjust the thickness Tt to the above range, and a higher effect is easily obtained.

[0075] The thickness Tt of the second portion and the number n of the second conductive polymer layers are determined from the Raman spectrum of a cross section parallel to the length direction of the anode body and perpendicular to the thickness direction (stacking direction of the second conductive polymer layers) in the electrolytic capacitor or capacitor element.

[0076] For measuring the Raman spectrum, a sample taken by the following procedure can be used. First, the electrolytic capacitor or capacitor element is embedded in a curable resin, and the curable resin is cured. The cured product is subjected to a polishing process or a cross-section polisher process to expose a cross section parallel to the length direction of the capacitor element (or anode body) and perpendicular to the thickness direction (lamination direction of the second conductive polymer layer) at the center of the width direction of the capacitor element (or anode body). In this way, a sample for measurement is obtained. In the exposed cross section of the sample, the Raman spectrum is measured for at least the portion on the second end side of the second portion.

[0077] In this specification, the Raman spectrum of the second portion is measured under the following conditions for the solid electrolyte present in the cross section of the porous portion at a predetermined position of the capacitor element. Raman spectrometer: NanoPhoton RamanFORCE PAV Diffraction grating: 300gr / mm Measurement wave number range: 200cm -1 More than 4500cm -1 below Temperature: 25℃ Laser light wavelength: 532nm Laser intensity: 1600W / cm 2 Exposure time: 8 seconds Number of times: 16 Coloring of conductive polymers: When the conjugated polymer is PEDOT, 1415 cm -1 Over 1460cm -1 The average intensity I1 in the range of 1100 cm -1 More than 1170cm -1 The Raman spectrum is colored so that the ratio I1 / I2 to the average intensity I2 in the following range is 1.0 or more and 2.0 or less. Portions with an I1 / I2 ratio of 1.7 or more are judged to be PEDOT. The average intensity I1 is the average intensity in the wavenumber range that covers the peak characteristic of conjugated polymers, and the average intensity I2 is the average intensity in the wavenumber range that corresponds to the baseline of the peak. In the case of other conjugated polymers, the conductive polymer portion is colored in the same manner as in the case of PEDOT.

[0078] In the Raman spectrum, the thickness of the solid electrolyte layer (second portion) formed on one main surface of the anode body is measured at the second end of the anode body (more specifically, at the endmost position of the second end). The thickness of the solid electrolyte layer (second portion) formed on the opposite main surface is measured. These thicknesses are then summed and averaged to obtain the thickness Tt (unit: μm) of the second portion.

[0079] In the above Raman spectrum, for example, the above coloring confirms the presence of layered second conductive polymer layers. The number of second conductive polymer layers formed on one main surface of the anode body is counted to determine n. The ratio Tt / n (unit: μm) is determined by dividing the thickness Tt by n.

[0080] As described above, the second portion preferably contains a water-soluble polymer. In particular, when the second portion contains a water-soluble polymer having an Mw of 50,000 or more and 800,000 or less, even if the number of layers n of the second conductive polymer layer is relatively small, the thickness Tt and the ratio Tt / n can be easily adjusted to the above range. Therefore, more excellent effects can be obtained in terms of reducing ESR, suppressing leakage current, and improving voltage resistance.

[0081] The content of the water-soluble polymer in the second portion may be 5% by mass or more and 20% by mass or less, or may be 10% by mass or more and 20% by mass or less. When the content of the water-soluble polymer is in such a range, a higher voltage resistance can be ensured and the leakage current can be further suppressed. Since it is easy to ensure high conductivity of the second portion, it is advantageous in further reducing the ESR.

[0082] The content of the water-soluble polymer in the second part can be obtained by using a sample of the second part (hereinafter referred to as sample A) taken from the cross section of the sample. More specifically, the second part is scraped off from the cross section, a predetermined amount of sample A is taken, and its mass is measured. The water-soluble polymer is extracted from sample A with water at 20°C to 40°C. The extract is concentrated, and the water-soluble polymer is identified by liquid chromatography mass spectrometry (LC-MS) or gas chromatography mass spectrometry (GC-MS). The concentration of the water-soluble polymer in the extract is obtained by a calibration curve method. The content (mass%) of the water-soluble polymer in the second part is obtained from this concentration and the mass of sample A. The above sample is prepared by embedding an electrolytic capacitor or a capacitor element in an acrylic resin, cutting the capacitor element at the center of the width direction in a direction parallel to the length direction to expose the cross section, and polishing it. The content of the water-soluble polymer in the first part can also be obtained in the same manner as the content in the second part.

[0083] (Cathode extraction layer) The cathode extraction layer must include at least a first layer that is in contact with the solid electrolyte layer and covers at least a portion of the solid electrolyte layer, and may include the first layer and a second layer that covers at least a portion of the first layer.

[0084] The first layer may be, for example, a layer containing conductive particles or a metal foil. The conductive particles may be, for example, at least one selected from conductive carbon and metal powder. The cathode part (more specifically, the cathode extraction layer) may include a layer containing metal powder (such as a metal particle-containing layer). The cathode extraction layer may be, for example, composed of a layer containing conductive carbon (carbon layer) as the first layer and a layer containing metal powder (such as a metal particle-containing layer) or metal foil as the second layer.

[0085] When the cathode extraction layer includes a metal foil or a metal particle-containing layer, the entire cathode extraction layer may be composed of the metal foil or the metal particle-containing layer, or at least one of the first layer and the second layer may be composed of the metal particle-containing layer.

[0086] An example of the conductive carbon is graphite (artificial graphite, natural graphite, etc.).

[0087] The layer containing metal powder as the second layer can be formed, for example, by laminating a composition containing metal powder on the surface of the first layer. Such a second layer can be, for example, a metal particle-containing layer formed using a paste containing metal powder and a resin binder. Although a thermoplastic resin can be used as the resin binder, it is preferable to use a thermosetting resin such as an imide resin or an epoxy resin. From the viewpoint of easily obtaining high conductivity of the second layer, silver-containing particles may be used as the metal powder. Examples of the silver-containing particles include silver particles and silver alloy particles. The second layer may contain one type of silver-containing particle or a combination of two or more types. The silver particles may contain a small amount of impurities.

[0088] When a metal foil is used as the first layer, the type of metal is not particularly limited. For the metal foil, it is preferable to use a valve metal (aluminum, tantalum, niobium, etc.) or an alloy containing a valve metal. If necessary, the surface of the metal foil may be roughened. The surface of the metal foil may be provided with a chemical conversion film, or may be provided with a coating of a metal (heterogeneous metal) different from the metal constituting the metal foil or a nonmetal. Examples of the heterogeneous metal or nonmetal include metals such as titanium and nonmetals such as carbon (conductive carbon, etc.).

[0089] The coating of the dissimilar metal or non-metal (eg, conductive carbon) may be the first layer, and the metal foil may be the second layer.

[0090] (Separator) When a metal foil is used for the cathode extraction layer, a separator may be disposed between the metal foil and the anode foil as the anode body. The separator is not particularly limited, and may be, for example, a nonwoven fabric containing fibers of cellulose, polyethylene terephthalate, vinylon, or polyamide (e.g., aliphatic polyamide, aromatic polyamide such as aramid).

[0091] (others) The electrolytic capacitor includes at least one capacitor element. The electrolytic capacitor may be of a wound type, and may be either a chip type or a stacked type. For example, the electrolytic capacitor may include a plurality of stacked capacitor elements. The electrolytic capacitor may also include two or more wound capacitor elements. The configuration of the capacitor element may be selected according to the type of the electrolytic capacitor.

[0092] [Manufacturing method of electrolytic capacitors] The electrolytic capacitor is formed, for example, by a manufacturing method including a first step of preparing an anode body, a second step of forming a dielectric layer on at least a portion of the surface of the anode body, and a third step of forming a solid electrolyte layer covering at least a portion of the dielectric layer. The manufacturing method may further include a fourth step of forming a cathode extraction layer covering the solid electrolyte layer. A capacitor element is formed by the first to third steps (or the fourth step). The manufacturing method of the electrolytic capacitor may further include a fifth step of connecting a lead terminal to the capacitor element, and a sixth step of sealing the capacitor element.

[0093] (1st step) In the first step, an anode body is prepared that includes a porous portion at least on the surface layer and has a first end and a second end. When the anode body is an anode foil, for example, as described above, an anode foil having a porous portion formed on the surface layer is obtained by etching a metal foil. The etching may be performed by electrolytic etching or chemical etching. When the anode body is a porous compact or a porous sintered body, for example, the anode body is obtained by molding particles containing a valve metal, or by sintering the molded body obtained by molding.

[0094] (2nd process) In the second step, a dielectric layer is formed on at least a portion of the surface of the anode body by, for example, anodizing a valve metal on the surface of the anode body by chemical conversion treatment or the like.

[0095] (3rd step) In the third step, a solid electrolyte layer is formed on the anode body having a dielectric layer so as to cover at least a part of the dielectric layer. The solid electrolyte layer is formed on the second end side of the anode body having a dielectric layer. As described above, the solid electrolyte layer has a first portion filled in the voids of the porous portion and a second portion protruding from the main surface of the anode body having a dielectric layer. The second portion includes n or more conductive polymer layers on one main surface of the anode body having a dielectric layer. n can be selected from the above-mentioned range. By the third step, a solid electrolyte layer is formed on the second end such that the thickness Tt and the ratio Tt / n of the second portion are in the above-mentioned range.

[0096] More specifically, the third step comprises: A sub-step A of treating a second end side of the anode body having a dielectric layer with a first treatment liquid containing a first conductive polymer or a precursor thereof; a sub-step B of treating a second end side of the anode body with a second treatment liquid containing at least a cationic agent after the sub-step A; a sub-step C of treating a second end side of the anode body with a third treatment liquid containing a second conductive polymer and a water-soluble polymer after the sub-step B; and sub-step D of repeating sub-step B and sub-step C. In sub-step D, sub-steps B and C may be repeated (n-1) times.

[0097] (Substep A) In sub-step A, a layer containing a first conductive polymer containing a conjugated polymer and a dopant (first conductive polymer layer) may be formed by chemically polymerizing and / or electrolytically polymerizing the precursor of the conjugated polymer on the dielectric layer using a first treatment liquid containing a precursor of the conjugated polymer and a dopant. The precursor may be at least one selected from monomers, oligomers, prepolymers, etc. of the conjugated polymer.

[0098] When a treatment liquid containing a precursor of a conjugated polymer is used, an oxidizing agent is used to polymerize the precursor. The oxidizing agent may be contained in the treatment liquid as an additive. The oxidizing agent may be applied to the anode body on which the dielectric layer is formed before or after the treatment liquid is brought into contact with the anode body. Examples of such oxidizing agents include Fe 3+ Examples of the oxidizing agent include compounds capable of generating oxidizing agent (such as ferric sulfate), persulfates (such as sodium persulfate and ammonium persulfate), and hydrogen peroxide. The oxidizing agent can be used alone or in combination of two or more kinds.

[0099] Alternatively, the first conductive polymer layer may be formed by contacting a first treatment liquid (solution or dispersion) containing the first conductive polymer with the dielectric layer. Usually, after contacting the first treatment liquid with the dielectric layer, a drying process (such as heat drying) is performed.

[0100] The application of the first treatment liquid to the anode body having the dielectric layer and polymerization (or drying) may be performed once or may be repeated multiple times. When repeated multiple times, the conditions such as the composition and viscosity of the first treatment liquid may be the same each time, or at least one of the conditions may be changed.

[0101] When the first conductive polymer layer contains a water-soluble polymer, the first treatment liquid may contain a water-soluble polymer. For the components contained in the first conductive polymer layer, the description of the solid electrolyte layer or the first portion can be referred to.

[0102] If necessary, sub-steps A and B may be repeated alternately prior to sub-step C.

[0103] (Substep B) In sub-step B, after sub-step A, the second end side of the anode body is treated with a second treatment liquid. The second treatment liquid contains at least a cationic agent. The second treatment liquid may contain a cationic agent and an anionic agent. The second treatment liquid may further contain a surfactant. For components contained in the second treatment liquid, the above description of the continuous or discontinuous layer can be referred to.

[0104] (Substep C) In sub-step C, after sub-step B, a third treatment liquid containing a second conductive polymer (and a water-soluble polymer) is brought into contact with the portion of the anode body on the second end side. After the third treatment liquid is brought into contact with the portion on the second end side, a drying process (such as heat drying) is usually performed. In this manner, a second conductive polymer layer containing the second conductive polymer (and a water-soluble polymer) is formed.

[0105] For the components contained in the third treatment liquid, the description of the solid electrolyte layer or the second portion can be referred to.

[0106] The concentration of the water-soluble polymer in the third treatment liquid may be 1% by mass or more and 15% by mass or less, or may be 5% by mass or more and 15% by mass or less. When the concentration of the water-soluble polymer is in such a range, it is easy to adjust the thickness Tt and the ratio Tt / n to the above-mentioned ranges.

[0107] (Substep D) In sub-step D, sub-step B and sub-step C are repeated (n-1) times, whereby the number n of layers of the second conductive polymer layer can be adjusted, and the thickness Tt of the second portion can be adjusted.

[0108] (4th step) In the fourth step, a cathode extraction layer is formed by a known method depending on the layer structure.

[0109] For example, when the cathode extraction layer includes a metal foil as the first layer or the second layer, the first layer or the second layer is formed by laminating the metal foil so as to cover at least a part of the solid electrolyte layer or the first layer. The first layer including conductive particles is formed, for example, by applying a conductive paste or liquid dispersion including conductive particles and, if necessary, a resin binder (such as a water-soluble resin or a curable resin) to the surface of the solid electrolyte layer. The second layer including metal powder is formed, for example, by applying a paste including metal powder and a resin binder to the surface of the first layer. In the process of forming the cathode extraction layer, a drying process, a heating process, or the like may be performed as necessary.

[0110] (5th step) In the fifth step, a lead terminal is connected to the capacitor element. In the capacitor element, one end of a cathode lead terminal may be electrically connected to the cathode extraction layer. The cathode lead terminal is bonded to the cathode extraction layer, for example, by applying a conductive adhesive to the cathode extraction layer and bonding the cathode lead terminal to the cathode extraction layer via the conductive adhesive. One end of an anode lead terminal may be electrically connected to the anode extraction portion of the anode body.

[0111] The other end of the anode lead terminal and the other end of the cathode lead terminal are each pulled out from the resin exterior body or the case when the capacitor element is sealed in step 6. The other end of each terminal exposed from the resin exterior body or the case is used for soldering to a board on which the electrolytic capacitor is to be mounted.

[0112] The fifth step is not limited to the case where the lead terminal is drawn out. In the fifth step, for example, the lead frame may be connected to the capacitor element. In this case, in the sixth step, the end face of the lead frame may be exposed from the outer surface of the resin exterior body. Also, in the fifth step, at least one end face of the anode part and the cathode part may be exposed from the outer surface of the resin exterior body in the sixth step. The end face of the lead frame exposed in the sixth step and the end faces of the anode part and the cathode part are electrically connected to an external electrode.

[0113] (6th step) The capacitor element is sealed using a resin exterior body or case. For example, the capacitor element and the resin material of the exterior body (e.g., uncured thermosetting resin and filler) may be housed in a mold, and the capacitor element may be sealed with the resin exterior body by transfer molding, compression molding, or the like. At this time, the other end side portions of the anode lead terminal and the cathode lead terminal connected to the anode lead drawn out from the capacitor element are exposed from the mold. Alternatively, the capacitor element may be housed in a bottomed case such that the other end side portions of the anode lead terminal and the cathode lead terminal are positioned on the opening side of the bottomed case, and the opening of the bottomed case may be sealed with a sealer to form an electrolytic capacitor.

[0114] FIG. 1 is a cross-sectional view showing a schematic structure of a solid electrolytic capacitor according to an embodiment of the present disclosure. FIG. 1 is a cross-sectional schematic view of a solid electrolytic capacitor in a direction parallel to both the length direction and the thickness direction of a capacitor element 2. As shown in FIG. 1, a solid electrolytic capacitor 1 includes a capacitor element 2, a resin outer casing 3 that seals the capacitor element 2, and an anode lead terminal 4 and a cathode lead terminal 5, at least a part of which is exposed to the outside of the resin outer casing 3. The anode lead terminal 4 and the cathode lead terminal 5 can be made of a metal such as copper or a copper alloy. The resin outer casing 3 has an outer shape of a substantially rectangular parallelepiped, and the solid electrolytic capacitor 1 also has an outer shape of a substantially rectangular parallelepiped.

[0115] Capacitor element 2 includes an anode body 6, a dielectric layer 7 covering the anode body 6, and a cathode portion 8 covering the dielectric layer 7. Cathode portion 8 includes a solid electrolyte layer 9 covering the dielectric layer 7, and a cathode extraction layer 10 covering the solid electrolyte layer 9. Cathode extraction layer 10 includes a carbon layer 11 covering the solid electrolyte layer 9, and a metal particle-containing layer 12 covering the carbon layer 11.

[0116] The anode body 6 includes a region facing the cathode portion 8 and a region not facing the cathode portion 8. Of the region of the anode body 6 not facing the cathode portion 8, an insulating separation portion (insulating region) 13 is formed in a strip-like shape covering the surface of the anode body 6 in a portion adjacent to the cathode portion 8, thereby restricting contact between the cathode portion 8 and the anode body 6. Of the region of the anode body 6 not facing the cathode portion 8, another part is electrically connected to the anode lead terminal 4 by welding. The cathode lead terminal 5 is electrically connected to the cathode portion 8 via an adhesive layer 14 formed of a conductive adhesive.

[0117] [Example] The present invention will be specifically described below based on examples and comparative examples, but the present invention is not limited to the following examples.

[0118] An electrolytic capacitor 1 shown in FIG. 1 was fabricated in the following manner, and its characteristics were evaluated. (1) Step of preparing anode body 6 (first step) An anode body 6 was produced by roughening both surfaces of an aluminum foil (thickness: 100 μm) used as a substrate by etching.

[0119] (2) Step of forming dielectric layer 7 (second step) The portion of the anode body 6 on the second end side was immersed in a chemical conversion solution, and a direct current voltage of 70 V was applied for 20 minutes to form a dielectric layer 7 containing aluminum oxide.

[0120] (3) Step of forming solid electrolyte layer 9 (third step) (3-1) Sub-step A 3,4-ethylenedioxythiophene monomer was added to an aqueous solution of polystyrene sulfonic acid (Mw: 75,000) under stirring, and then oxidizing agents (iron sulfate (III) and sodium persulfate) were added to carry out chemical oxidative polymerization. The resulting polymerization solution was filtered through an ion exchange device to remove impurities, yielding a solution containing poly3,4-ethylenedioxythiophene (PEDOT) as a conjugated polymer and polystyrene sulfonic acid (PSS) as a dopant.

[0121] The obtained solution was mixed with pure water, homogenized with a high-pressure homogenizer, and filtered to prepare a first treatment liquid in the form of a dispersion. The concentration of the first conductive polymer (PEDOT and PSS) in the first treatment liquid was 2% by mass.

[0122] The portion on the second end side of the anode body 6 having the dielectric layer 7 obtained in (2) above was immersed in the first treatment liquid, then removed from the first treatment liquid, and further dried for 10 to 30 minutes at 120° C. By repeating the immersion in the first treatment liquid and drying once more, at least a part of the first portion containing the first conductive polymer was formed so as to cover the surface of the dielectric layer 7 and to fill at least a part of the recesses in the porous portion.

[0123] (3-2) Sub-step B A second treatment liquid was prepared by dissolving N,N-dimethyloctylamine (cationic agent) and a copolymer of styrenesulfonic acid and acid phosphooxyethyl acrylate (P(=O)(OH)2-O-CH2CH2-OC(=O)-CH=CH2) (anionic agent) in pure water. The concentration of the cationic agent in the second treatment liquid was 0.05 mol / L, and the concentration of the anionic agent was 0.03 mol / L.

[0124] The portion of the second end side of the anode body 6 treated in sub-step A was immersed in the second treatment liquid, and then taken out and dried at 100°C for 3 minutes, thereby adhering the cationic agent and the anionic agent to the surface of the first conductive polymer.

[0125] The anionic agent used in the second treatment liquid was prepared as follows. A monomer solution was prepared by adding and mixing sodium styrenesulfonate and acid phosphooxyethyl acrylate to a predetermined amount of pure water. At this time, sodium styrenesulfonate and acid phosphooxyethyl acrylate were used in such a ratio that the copolymerization ratio (molar ratio) of styrenesulfonic acid and acid phosphooxyethyl acrylate in the copolymer was 75:25. A predetermined amount of ammonium persulfate (oxidizing agent) was added to the monomer solution under stirring, and a polymerization reaction was carried out over 8 hours. Pure water and ion exchange resin were added to the obtained polymerization liquid, and the mixture was stirred and filtered to carry out a purification treatment. This purification treatment was repeated several times to finally obtain the above copolymer. The molecular weight of the copolymer was measured by GPC, and Mw was 83,000.

[0126] (3-3) Substep C A solution containing PEDOT and PSS was obtained in the same manner as in (3-1) above. Pure water and, if necessary, an acrylic acid-methacrylic acid copolymer (water-soluble polymer) having the Mw shown in Table 1 were added to the obtained solution, which was then homogenized with a high-pressure homogenizer and filtered through a filter to prepare a third treatment liquid in the form of a dispersion. The concentration of the second conductive polymer in the third treatment liquid was 4 mass %, and the concentration of the water-soluble polymer was 11 mass %.

[0127] The portion on the second end side of anode body 6 obtained in sub-step B was immersed in the third treatment liquid, then taken out and further dried for 10 to 30 minutes at 120° C. In this manner, one second conductive polymer layer was formed.

[0128] (3-4) Substep D The second end side portion of the anode body 6 obtained in sub-step C was subjected to sub-step B using the above-mentioned second treatment liquid. The second end side portion of the anode body 6 obtained in this sub-step B was subjected to sub-step C using the above-mentioned third treatment liquid. If necessary, this sub-step B and sub-step C were further repeated alternately. In sub-step D, sub-step B and sub-step C were each repeated a total of (n-1) times to form a solid electrolyte layer 9 having n layers of second conductive polymer layers as shown in Table 1. Most of the second conductive polymer layer constitutes the second portion formed on the main surface of the anode body 6, and a part of the second conductive polymer layer may be filled in the recesses of the porous portion of the anode body 6.

[0129] In the examples in which the second portion contains a water-soluble polymer, the content of the water-soluble polymer in the second portion, determined by the procedure described above, was 10% by mass to 20% by mass.

[0130] (4) Forming the Cathode Extraction Layer 10 The portion on the second end side of anode body 6 obtained in (3) above was immersed in a dispersion liquid in which graphite particles were dispersed in water, removed from the dispersion liquid, and then dried to form a first layer (carbon layer) 11 at least on the surface of solid electrolyte layer 9. Drying was performed at 130 to 180° C. for 10 to 30 minutes.

[0131] Next, a silver paste containing silver particles and a binder resin (epoxy resin) was applied to the surface of the first layer 11 and heated at 150 to 200°C for 10 to 60 minutes to harden the binder resin, thereby forming a second layer (metal particle-containing layer) 12. In this way, a cathode extraction layer 10 composed of the first layer 11 and the second layer 12 was formed. Capacitor element 2 was produced as described above.

[0132] (5) Assembly of electrolytic capacitors Cathode extraction layer 10 of capacitor element 2 obtained in (4) above was joined to one end of cathode lead terminal 5 via an adhesive layer made of a conductive adhesive. A first end of anode body 6 protruding from capacitor element 2 was joined to one end of anode lead terminal 4 by laser welding. Next, a resin outer casing 3 made of insulating resin was formed around the capacitor element 2 by transfer molding. At this time, the other end of the anode lead terminal 4 and the other end of the cathode lead terminal 5 were pulled out from the resin outer casing 3. In this way, the electrolytic capacitor 1 was completed. In the same manner as above, a total of 20 electrolytic capacitors 1 were produced for each example.

[0133] (6) Evaluation The electrolytic capacitor was used to carry out the following evaluations.

[0134] (a) Thickness Tt and ratio Tt / n The thickness Tt (μm) of the second portion and the number n of layers of the second conductive polymer layer were determined by the procedure described above, and the ratio Tt / n (μm) was calculated from these.

[0135] (b) Initial capacitance (Cap) and ESR In an environment of 20°C, the initial capacitance (μF) of each electrolytic capacitor at a frequency of 120Hz was measured using a four-terminal LCR meter, and the initial ESR (mΩ) at a frequency of 100kHz was also measured.The average values ​​of the initial capacitance (Cap) and ESR of the 20 electrolytic capacitors were then calculated.

[0136] (c) Leakage current (LC) A 1 kΩ resistor was connected in series to the electrolytic capacitor, and the leakage current (μA) was measured after applying a rated voltage of 10 V from a DC power supply for 20 seconds, and the average value for 20 electrolytic capacitors was calculated.

[0137] (d) Voltage resistance Of the electrolytic capacitors whose LC was measured, 10 electrolytic capacitors were subjected to voltage application at a rate of 1.0 V / sec, and the breakdown withstand voltage (V) at which an overcurrent of 0.5 A flows was measured. The average value for the 10 electrolytic capacitors was then calculated.

[0138] The evaluation results are shown in Table 1. In Table 1, A1 to A3 are examples, and B1 to B5 are comparative examples.

[0139] [Table 1]

[0140] As shown in Table 1, in the embodiment, while securing a relatively high capacitance and a low ESR, the leakage current can be suppressed to a low level, and a relatively high voltage resistance can be secured, as compared with the comparative example. This is because the thickness Tt and the ratio Tt / n of the second portion satisfy 18.0 μm≦Tt≦50.0 μm and 9.0 μm≦Tt / n≦12.5 μm, respectively. When Tt<18.0 μm, the voltage resistance is significantly reduced (comparison of B2 and B4 with A3). Even when Tt<18.0 μm, when the number n of the second conductive polymer layers is 1, the leakage current is relatively small (B4). This is considered to be because the number of times of heating and drying is small, so that the stress due to thermal shrinkage is suppressed and the occurrence of defects in the dielectric layer is suppressed. However, when Tt<18.0 μm and n=2, the leakage current is significantly large (comparison of B4 with B2). This is thought to be because, in addition to the small Tt, greater stress is applied to the dielectric layer due to thermal contraction, making it more susceptible to defects. Also, when Tt>50μm, high voltage resistance is obtained, but the leakage current is large (comparison of B1 and B5 with A2). This is thought to be because a larger n is required to increase the thickness Tt, and the increased number of heating and drying processes increases the stress due to thermal contraction, making the dielectric layer more susceptible to defects.

[0141] Even when 18.0μm≦Tt≦50.0μm is satisfied, in the case of Tt / n<9.0μm, the voltage resistance is low and the ESR is increased compared to the case of Tt / n≧9.0μm (comparison of B3 with A1 and A2). In the case of 18.0μm≦Tt≦50.0μm and Tt / n<9.0μm, even if the second conductive polymer layer can ensure a certain degree of conductivity, n becomes large. Therefore, the interface resistance between adjacent second conductive polymer layers becomes large. Therefore, it is considered that the conductivity of the second portion as a whole becomes low and the ESR increases. In addition, from the comparison of B3 with A1 and A2, when the second conductive polymer layer contains a water-soluble polymer, a conductive polymer layer with a relatively uniform thickness is easily formed, and the voltage resistance tends to be further increased.

[0142] In addition, when the Mw of the water-soluble polymer is 50,000 or more and 800,000 or less, it is easier to adjust the ratio Tn / n to the range of 9.0 μm≦Tt / n≦12.5 μm, compared to when Mw is outside this range. Therefore, even if n is relatively small, it is easier to adjust the thickness Tt to satisfy 18.0 μm≦Tt≦50.0 μm. Therefore, it is easier to reduce the stress applied to the dielectric layer due to the thermal contraction of the second conductive polymer layer, and the total interfacial resistance between adjacent second conductive polymer layers can be reduced. Therefore, it is easier to further reduce the leakage current, and higher voltage resistance can be obtained. In addition, it is easier to ensure high conductivity of the entire second portion, so that a low ESR can be easily obtained. Furthermore, when the Mw of the water-soluble polymer is 50,000 or more and 800,000 or less, it is easier to form a second conductive polymer layer with relatively uniform film quality and thickness. [Industrial Applicability]

[0143] The present disclosure provides a high-quality electrolytic capacitor, which can be used for a variety of purposes. [Explanation of symbols]

[0144] 1: Electrolytic capacitor 2: Capacitor element 3: Resin exterior body 4: Anode lead terminal 5: Cathode lead terminal 6: Anode body 7: Dielectric layer 8: Cathode 9: Solid electrolyte layer 10: Cathode extraction layer 11: 1st layer 12:Second layer 13: Isolation section (insulating area) 14: Adhesive layer

Claims

1. at least one capacitor element including an anode body including a porous portion at least in a surface layer thereof, a dielectric layer covering at least a portion of a surface of the anode body, and a solid electrolyte layer covering at least a portion of the dielectric layer; the anode body has a first end and a second end opposite the first end, the solid electrolyte layer is formed on the second end side of the anode body having the dielectric layer, and has a first portion filling voids in the porous portion and a second portion protruding from a main surface of the anode body having the dielectric layer, the second portion includes n or more conductive polymer layers on one main surface of the anode body having the dielectric layer, n is an integer of 2 or more, At the second end, a thickness (Tt) of the second portion on one main surface of the anode body having the dielectric layer satisfies 18.0 μm≦Tt≦50.0 μm, An electrolytic capacitor in which Tt / n satisfies 9.0 μm≦Tt / n≦12.5 μm.

2. 2. The electrolytic capacitor of claim 1, wherein n is 4 or less.

3. 3. The electrolytic capacitor according to claim 1, wherein the thickness Tt satisfies 20.0 μm<Tt.

4. The second portion includes a water-soluble polymer, 3. The electrolytic capacitor according to claim 1, wherein the water-soluble polymer has a weight average molecular weight of 50,000 or more and 800,000 or less.

5. 5. The electrolytic capacitor according to claim 4, wherein the content of the water-soluble polymer in the second portion is 10% by mass or more and 20% by mass or less.

6. the second portion includes at least one continuous or discontinuous layer interposed between adjacent conductive polymer layers; 3. The electrolytic capacitor of claim 1, wherein the continuous or discontinuous layer comprises at least a cationic agent.

7. A first step of preparing an anode body including a porous portion at least in a surface layer and having a first end and a second end opposite to the first end; A second step of forming a dielectric layer on at least a portion of the surface of the anode body; and a third step of forming a solid electrolyte layer covering at least a portion of the dielectric layer, the solid electrolyte layer is formed on the second end side of the anode body having the dielectric layer, and has a first portion filling voids in the porous portion and a second portion protruding from a main surface of the anode body having the dielectric layer, the second portion includes n or more conductive polymer layers on one main surface of the anode body having the dielectric layer, n is an integer of 2 or more, The third step comprises: a sub-step A of treating the second end side of the anode body having the dielectric layer with a first treatment liquid containing a first conductive polymer or a precursor thereof; a sub-step B of treating the second end side of the anode body with a second treatment liquid containing at least a cationic agent after the sub-step A; a sub-step C of treating the second end side of the anode body with a third treatment liquid containing a second conductive polymer and a water-soluble polymer after the sub-step B; a sub-step D of repeating the sub-steps B and C; At least the third step forms the solid electrolyte layer at the second end such that a thickness (Tt) of the second portion on one main surface of the anode body having the dielectric layer satisfies 18.0 μm≦Tt≦45.0 μm and Tt / n satisfies 9.0 μm≦Tt / n≦12.5 μm.

8. 8. The method for producing an electrolytic capacitor according to claim 7, wherein in said sub-step D, said sub-step B and said sub-step C are repeated (n-1) times.

9. 9. The method for producing an electrolytic capacitor according to claim 7, wherein n is 2 or more and 4 or less.

10. 9. The method for producing an electrolytic capacitor according to claim 7, wherein the water-soluble polymer has a weight average molecular weight of 50,000 or more and 800,000 or less.

11. 9. The method for manufacturing an electrolytic capacitor according to claim 7, wherein a concentration of the water-soluble polymer in the third treatment liquid is 1% by mass or more and 15% by mass or less.

Citation Information

Patent Citations

  • Method for manufacturing solid electrolytic capacitor

    WO2014087617A1

  • Electrolytic capacitor and method for producing same

    WO2021132223A1